2013
DOI: 10.1002/ijc.28273
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in T cell/histiocyte rich large B cell lymphoma strongly express metal-binding proteins and show a bi-activated phenotype

Abstract: Abundant macrophage infiltration in tumors often correlates with a poor prognosis. T cell/histiocyte rich large B cell lymphoma (THRLBCL) is a distinct aggressive B cell lymphoma entity showing a high macrophage content. To further elucidate the role of tumor-associated macrophages in THRLBCL, we performed gene expression profiling of microdissected histiocyte subsets of THRLBCL, nodular lymphocyte predominant Hodgkin lymphoma (NLPHL), Piringer lymphadenitis, sarcoidosis, nonspecific lymphadenitis and monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…We cannot exclude that this result is influenced by technical limitations, like a strong amplification of the RNA before array hybridization, causing loss of some differentially expressed genes. However, applying the same technique, we obtained numerous and up to 21-fold differentially expressed genes in another study of microdissected cells [12]. Both the unsupervised hierarchical clustering as well as the principal component analysis revealed that there is often more heterogeneity in global gene expression between two cases of one of the three lymphoma entities analyzed than between cases of different entities.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We cannot exclude that this result is influenced by technical limitations, like a strong amplification of the RNA before array hybridization, causing loss of some differentially expressed genes. However, applying the same technique, we obtained numerous and up to 21-fold differentially expressed genes in another study of microdissected cells [12]. Both the unsupervised hierarchical clustering as well as the principal component analysis revealed that there is often more heterogeneity in global gene expression between two cases of one of the three lymphoma entities analyzed than between cases of different entities.…”
Section: Discussionmentioning
confidence: 92%
“…Both BAT3/ BAG6 as well as UBD/FAT10 expression was shown to be increased during inflammatory response [21,43]. This may be caused by the release of proinflammatory factors from macrophages of THRLBCL [12]. Moreover, HIGD1A, an important player in the maintenance of normal mitochondrial function in hypoxia [17,44,45], was expressed in a subset of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Hodgkin and Reed-Sternberg cells are known to express several additional markers usually expressed by antigenpresenting cells. [46][47][48] Although Hodgkin and ReedSternberg cells have usually lost their B-cell phenotype, they have maintained the features for an interaction with T cells, which is not observed in the tumor cells of ALK À anaplastic large cell lymphoma. Interestingly, Hodgkin lymphoma cases with granzyme B expression were less frequently positive for MDC/CCL22 and CD83 than conventional classical Hodgkin lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Whole tissue sections were stained for CD83, MDC/CCL2, TUBB2B, STAT3, and CAPN2 using the Peroxidase-FLEX EnVision Kit (Dako) as described previously. 22,23 The antibodies used, dilutions, and providers are listed in Table 2. Antigen unmasking was performed for 3 min in a pressure cooker or microwave in Tris-EDTA at pH 8.0 or citrate buffer at pH 6.0.…”
Section: Microarray Data Analysis and Selection Of Target Genesmentioning
confidence: 99%